The Effect Of Legal Nigilism And Legal Idealism On The Level Of Legal Consciousness And Culture - Makhmut, Utemuratov (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article describes the system of tasks to improve the legal culture and the elimination of legalnihilism and legal idealism, still found in the minds and activities of members of society.And also about how legalnihilism and legal idealism, which feed each other, as a common beneficial phenomenon of legal illiteracy.